Protección del desarrollo de productos elaborados en la carrera de agroindustria, a través del secreto industrial de la Salchicha Andino PAVIS. - Molina Suáres, Mishell Carolina (2022)
At project developed the industrial secret protection of Andino Pavis sausage, for this the most important information of the research work Andino Pavis sausage was collected, that it was done in Technical University of Cotopaxi library, which flow diagrams, production processes, product formulation, were obtained from documentation. Next, turned to a legal professional, who directed legal process to necessary register for industrial secret, the stages were to formalize the product recipe (Third Notary), Subsequently, an application was filed with National Service for Intellectual Rights (SENADI), together with deed protocolization of the recipe, they were in charge to registering the industrial secret, intellectual property to Technical University of Cotopaxi, resulting on protection of the guarantee industrial secret, and thus preventing other people who have access to this information from replicating or using this recipe, without having previously made an agreement with the institution, holder of this right.